Archeterokrohnia docrickettsae (Chaetognatha: Phragmophora: Heterokrohniidae), a new species of deep-sea arrow worm from the Gulf of California - Thuesen, Erik V.; Haddock, Steven H.d. (Zootaxa, 2013)
A new species of deep-sea chaetognath, Archeterokrohnia docrickettsae n. sp. is described from a single specimen captured by the ROV Doc Ricketts 2 m above the sea floor at 3245 m depth in the Pescadero Basin of the Gulf of California, Mexico. This is the first record of a living specimen of Archeterokrohnia and the second known occurrence of Archeterokrohnia in the Pacific Ocean. In life, the head and trunk sections were orange, while the tail section was translucent, a unique colour pattern not before seen in chaetognaths. Observations of its swimming behaviour in situ are given. Comparisons are made with the three other species of Archeterokrohnia. At 28.5 mm in length, this is the largest known species of the genus. An artificial key to the four species of Archeterokrohnia is presented.